The combination of LILRB4-targeting NK cell engagers and cGAS–STING agonists enhances the anti–multiple myeloma immune activity of NK cells - Meng Li; Yuwei Zhao; Lizhou Zhao; Xue Chen; Jianxun Kang; Aiping Tong; Chen Yang; Ping Wang; Minjun Yang; Kejiang Wang; Jialiang Gao; Ying Li; et al. (PLoS ONE, 2025)
Although significant progress has been made in immune-targeted therapy for multiple myeloma (MM), it remains highly recurrent and incurable. Consequently, there is still an urgent need to develop more effective strategies against the recurrent and refractory tumor subsets. LILRB4, which is expressed on MM and Myeloid-Derived Suppressor Cells (MDSC) and plays an important role in promoting tumor progression and regulating the immuno-suppressive microenvironment. Therefore, it is an attractive target for MM treatment. We developed a bispecific natural killer cell engager (BiKE), LILRB4/CD16A, to mediate NK cell-mediated lysis of MM cells. BiKE combined with CD16A strongly activated NK cells derived from human peripheral blood, and at the same time, BiKE bridged tumor cells to NK cells and promoted NK cytotoxicity, showing significant antitumor activity against LILRB4-high MM cells. NK cell cytotoxicity was further enhanced by the combined stimulation of innate immunity using cGAS-STING signaling agonists. In xenograft MM tumor models in immunodeficient mice, NK cells derived from human peripheral blood and expanded in vitro were combined with BiKE and cGAS-STING signaling agonists, demonstrating effective anti-tumor activity and inhibition of MM cell proliferation. Collectively, the combination of cGAS-STING agonists and LILRB4-targeting NK cell engagers offers a promising approach for treating relapsed/refractory MM.